EDUKASI PERANAN TEKNOLOGI DALAM PEMBELAJARAN DI SMK ABDURRAB MENGHADAPI ERA SOCIETY 5.0 - Elvitaria Luluk Luluk; Diki Arisandi; Seri Hartati; Liza Trisnawati; Lasiah Susanti (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
SMK Abdurrab Vocational School is a vocational high school located in the city of Pekanbaru. This school has been established since 1994, Abdurrab Vocational School has received many awards both provincial and national. As a health vocational high school, it really needs assistance related to technology so that learning can run smoothly and can produce human resources (HR) that are superior and able to adapt in the Society 5.0 era. The role of technology in learning cannot be denied as one of the tools that can help schools to be able to overcome future problems. To prepare human resources who are superior and able to adapt in the era of society 5.0, teachers need to be given education on how to compile and modify creative and innovative learning media. In this education, teachers will be given an explanation of what technologies can be used to assist teaching at Abdurrab Vocational High School with the hope that Abduurrab Vocational High School is ready to face challenges in the era of society 5.0. Then the teacher can make learning media according to the appropriate learning technology with the era of society 5. After carrying out this Community Education activity, Abdurrab Vocational School teachers can implement it in the form of applying the use of technology to learning media so as to create an attractive, interesting, fun teaching and learning process in the classroom